Motivasi Kerja, Internal Locus Of Control dan Kepuasan Kerja Pada Karyawan Bagian Marketing Dan Supporting di PT X Cabang Surabaya - Hastuti, Weni; Farid, M. (Persona:Jurnal Psikologi Indonesia, 2015)
Research that takes the subject 100 employees at PT. X in Surabaya branch fromand marketing supporting division to find the motivation to work and internal locus ofcontrol and job satisfaction in a correlational study. Data collected through questionnairesand analyzed by multiple regression test. The results show the value of F = 3.449; p =0.0036 (p <0.05), which means that work motivation and internal locus of controlcombination has a significant correlation with employees job satisfaction. It can besaid that the hypothesis that states motivation and internal locus of control on employeesat the marketing and supporting division have a relationship with employee satisfaction,that means it can be accepted. The value of R2 = 0.066 describe motivation and internallocus of control simultaneously have contributed effectively to job satisfaction up to 6.6%and that is a quite low in value. Partial test results of work motivation are t = 2.353; p= 0.021 (p <0.05), which means there is a significant positive correlation between workmotivation and job satisfaction, while the result of internal locus of control are = -0.572;p = 0.568 (p> 0.05), that means there is no correlation between the internal locus ofcontrol and job satisfaction.Keywords : Job satisfaction, work motivation, internal locus of control